The immunoglobulin E-allergen interaction: a target for therapy of type I allergic diseases. - Valenta, R; Almo, S; Ball, T; Dolecek, C; Steinberger, P; Laffer, S; Eibensteiner, P; Flicker, S; Vrtala, S; Spitzauer, S; Valent, P; Denepoux, S; et al. (1998)
The interaction of immunoglobulin E and otherwise harmless antigens (allergens) leads in sensitized individuals through effector cell activation to the immediate induction of a cascade of inflammatory reactions, the hallmark of type I allergy. Recently, the molecular and structural characterization of allergens, specific IgE antibodies and their epitopes has made rapid progress. Here we discuss active and passive strategies for therapy of type I allergy, which are based on interfering with the IgE-allergen interaction.